L2 공간에서 트랜슬레이션, 모듈레이션, 다일레이션의 역작용소

L2 공간에서 트랜슬레이션, 모듈레이션, 다일레이션의 역작용소

Inverse of Translation, Modulationm, and Dilation in L2 Space

정리1

$T_{a}, E_{b}, D_{c}$ 는 유니터리며, 역작용소는 다음과 같다.

$$ T_{a}^{-1} = T_{-a} = \left( T_{a} \right)^{ \ast } $$

$$ E_{b}^{-1} = E_{-b} = \left( E_{b} \right)^{ \ast } $$

$$ D_{c}^{-1} = D_{1/c} = \left( D_{c} \right)^{ \ast } $$

이때 $T_{a}, E_{b}, D_{c}$ 는 각각 $L^{2}$ 에서 정의된 트랜슬레이션, 모듈레이션, 다일레이션이다.

증명

트랜슬레이션

$t := x - a$ 와 같이 치환하면

$$ \begin{align*} \langle T_{a} f , g \rangle =& \int_{-\infty}^{\infty} f \left( x - a \right) \overline{g \left( x \right)} dx \\ =& \int_{-\infty}^{\infty} f \left( t \right) \overline{g \left( t + a \right)} dt \\ =& \langle f , T_{-a} g \rangle \\ =& \langle f , T_{a}^{ \ast } g \rangle \end{align*} $$

$T_{-a} = T_{a}^{ \ast }$ 이므로

$$ T_{a} T_{a}^{ \ast } = T_{a} T_{-a} = I = T_{-a} T_{a} = T_{a}^{ \ast } T_{a} $$

모듈레이션

$\displaystyle e^{2 \pi i b x} = \overline{e^{-2 \pi i b x}}$ 이므로

$$ \begin{align*} \langle E_{b} f , g \rangle =& \int_{-\infty}^{\infty} e^{2 \pi i b x} f \left( x \right) \overline{g \left( x \right)} dx \\ =& \int_{-\infty}^{\infty} f \left( x \right) \overline{e^{-2 \pi i b x}} \overline{ g \left( x \right)} \\ =& \int_{-\infty}^{\infty} f \left( x \right) \overline{ e^{2 \pi i (-b) x} g \left( x \right)} \\ =& \langle f , E_{-b} g \rangle \\ =& \langle f , E_{b}^{ \ast } g \rangle \end{align*} $$

$E_{-b} = E_{b}^{ \ast }$ 이므로

$$ E_{b} E_{b}^{ \ast } = E_{b} E_{-b} = I = E_{-b} E_{b} = E_{b}^{ \ast } E_{b} $$

다일레이션

$\displaystyle t := {{ x } \over { c }}$ 와 같이 치환하면

$$ \begin{align*} \langle D_{c} f , g \rangle =& \int_{-\infty}^{\infty} {{ 1 } \over { \sqrt{c} }} f \left( {{ x } \over { c }} \right) \overline{g \left( x \right)} dx \\ =& \int_{-\infty}^{\infty} f \left( t \right) {{ 1 } \over { \sqrt{c} }} \overline{g \left( ct \right)} c dt \\ =& \int_{-\infty}^{\infty} f \left( t \right) \overline{ \sqrt{c} g \left( ct \right)} c dt \\ =& \langle f , D_{1/c} g \rangle \\ =& \langle f , D_{c}^{ \ast } g \rangle \end{align*} $$

$D_{1/c} = D_{c}^{ \ast }$ 이므로

$$ D_{c} D_{c}^{ \ast } = D_{c} D_{1/c} = I = D_{1/c} D_{c} = D_{c}^{ \ast } D_{c} $$


  1. Ole Christensen, Functions, Spaces, and Expansions: Mathematical Tools in Physics and Engineering (2010), p121 ↩︎

댓글